If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(3x-2)-3(x-4)=7x+20
We move all terms to the left:
4(3x-2)-3(x-4)-(7x+20)=0
We multiply parentheses
12x-3x-(7x+20)-8+12=0
We get rid of parentheses
12x-3x-7x-20-8+12=0
We add all the numbers together, and all the variables
2x-16=0
We move all terms containing x to the left, all other terms to the right
2x=16
x=16/2
x=8
| 13t-10=46 | | 6x+3x=15+21 | | .84=x-27/7 | | F(n+1)=4 | | F(n+1)=1/2 | | 1/20=x/5000 | | -0.2x+x=180-6 | | 3.4x-9.04=8.3 | | 7/21=x/18 | | 7/21=b/18 | | 3(13.7r-1.2)=47 | | 8x-9.02=2.5 | | 3y-13/y+40=23/10 | | 3x-13/x+40=23/10 | | 8/9-3=x | | .03(x)=5 | | 4/9-3=x | | 3/5x-3=1/2x+5 | | x/5=x+3/20 | | -4=-17×x | | 10/10+x=35/56 | | K/3+3k/10=3/2 | | 120+2x=340 | | (3x+8)+(x+12)=360 | | -6b+4+4b=-3b+12 | | 6x+185=8x-207 | | x-7/2=4/3 | | 0=12x^2-24x-16 | | 2(x-3)-4=15-(x+6) | | 2x+(x+1)+(x+35)=180 | | 10/a=15/24 | | x-1/2x+3=4/13 |